Vitamin D, cardiovascular disease and mortality - Pilz, Stefan; Tomaschitz, Andreas; März, Winfried; Drechsler, Christiane; Ritz, Eberhard; Zittermann, Armin; Cavalier, Etienne; Pieber, Thomas R.; Lappe, Joan M.; Grant, William B.; Holick, Michael F.; Dekker, Jacqueline M. (Clinical endocrinology, 2011)
A poor vitamin D status, i.e. low serum levels of 25-hydroxyvitamin D [25(OH)D], is common in the general population. This finding is of concern not only because of the classic vitamin D effects on musculoskeletal outcomes, but also because expression of the vitamin D receptor (VDR) and vitamin D metabolizing enzymes in the heart and blood vessels suggests a role of vitamin D in the cardiovascular system. VDR-knockout mice suffer from cardiovascular disease (CVD), and various experimental studies suggest cardiovascular protection by vitamin D, including antiatherosclerotic, anti-inflammatory and direct cardio-protective actions, beneficial effects on classic cardiovascular risk factors as well as suppression of parathyroid hormone (PTH) levels. In epidemiological studies, low levels of 25(OH)D are associated with increased risk of CVD and mortality. Data from randomized controlled trials (RCTs) are sparse and have partially, but not consistently, shown some beneficial effects of vitamin D supplementation on cardiovascular risk factors (e.g. arterial hypertension). We have insufficient data on vitamin D effects on cardiovascular events, but meta-analyses of RCTs indicate that vitamin D may modestly reduce all-cause mortality. Despite accumulating data suggesting that a sufficient vitamin D status may protect against CVD, we still must wait for results of large-scale RCTs before raising general recommendations for vitamin D in the prevention and treatment of CVD. In current clinical practice, the overall risks and costs of vitamin D supplementation should be weighed against the potential adverse consequences of untreated vitamin D deficiency.